2013
DOI: 10.1371/journal.pone.0077348
|View full text |Cite
|
Sign up to set email alerts
|

A Passive Exoskeleton Can Push Your Life Up: Application on Multiple Sclerosis Patients

Abstract: In the present study, we report the benefits of a passive and fully articulated exoskeleton on multiple sclerosis patients by means of behavioral and electrophysiological measures, paying particular attention to the prefrontal cortex activity. Multiple sclerosis is a neurological condition characterized by lesions of the myelin sheaths that encapsulate the neurons of the brain, spine and optic nerve, and it causes transient or progressive symptoms and impairments in gait and posture. Up to 50% of multiple scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
(24 reference statements)
4
22
0
Order By: Relevance
“…We confirmed that this newly discovered components, compared to no-go, is larger in the go condition as previously described by our group (Di Russo et al, 2013a,b; Berchicci et al, 2014). The neural generator of the pP was localized in the anterior Insula in a study combining fMRI and ERP data collected with the same task used in the present study (Di Russo et al, 2013b), and its function would be to trigger the response when enough information are accumulated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We confirmed that this newly discovered components, compared to no-go, is larger in the go condition as previously described by our group (Di Russo et al, 2013a,b; Berchicci et al, 2014). The neural generator of the pP was localized in the anterior Insula in a study combining fMRI and ERP data collected with the same task used in the present study (Di Russo et al, 2013b), and its function would be to trigger the response when enough information are accumulated.…”
Section: Discussionsupporting
confidence: 93%
“…The positivity enhancement over the frontopolar derivations was closely associated to the go condition as triggering the response execution (Berchicci et al, 2014): it started bilaterally 80 ms after the stimulus and peaked at 300–350 ms, as also reported in a study with neurological patients (Di Russo et al, 2013a). …”
Section: Methodssupporting
confidence: 57%
“…The pP1, peaking at 180 ms, seems to reflect perceptual awareness process; otherwise, the pP2 emerging at around 300 ms after the stimulus (i.e. in the course of the decision process, about 100-150 ms before response emission), seems to reflect the accumulation of sensory evidence for categorizing the perceived stimulus Di Russo et al, 2013Perri et al, 2014bPerri et al, ,c, 2015Perri et al, , 2016Sulpizio et al, 2017), consistent with studies associating the insular activation to the stimulus-response (S-R) coupling to guide response selection (Boettiger and D'Esposito, 2005). Figure 13 shows the ERP for externally-triggered DRT in a 3 s time windows were the pN, the BP, the pP1 and the pP2 are labeled.…”
Section: Prefrontal Activitymentioning
confidence: 95%
“…Finally, we evaluated two other post-stimulus components preceding the response emission: the well-know N2 component, usually peaking at 250-300 ms after the stimulus, and the recently described prefrontal positivity (pP) peaking about 300 ms after stimulus onset Di Russo et al, 2013a, 2013bLucci et al, 2013;. In the context of a Go/No-go task, the fronto-central N2 was mainly related to the inhibitory processing because it is usually enhanced when motor responses are correctly inhibited, such as in the case of No-go trials (e.g., Van Boxtel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%